Crosstalk Between Intestinal Microbiota Derived Metabolites and Tissues in Allogeneic Hematopoietic Cell Transplantation - Fujiwara, Hideaki (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an evidence based- cellular immunotherapy for hematological malignancies. Immune reactions not only promote graft-versus-tumor effects that kill hematological malignant cells but also graft-versus-host disease (GVHD) that is the primary complication characterized by systemic organ damages consisting of T-cells and antigen presenting cells (APCs) activation. GVHD has long been recognized as an immunological reaction that requires an immunosuppressive treatment targeting immune cells. However immune suppression cannot always prevent GVHD or effectively treat it once it has developed. Recent studies using high-throughput sequencing technology investigated the impact of microbial flora on GVHD and provided profound insights of the mechanism of GVHD other than immune cells. Allo-HSCT affects the intestinal microbiota and microbiome-metabolome axis that can alter intestinal homeostasis and the severity of experimental GVHD. This axis can potentially be manipulated via dietary intervention or metabolites produced by intestinal bacteria affected post-allo-HSCT. In this review, we discuss the mechanism of experimental GVHD regulation by the complex microbial community-metabolites-host tissue axis. Furthermore, we summarize the major findings of microbiome-based immunotherapeutic approaches that protect tissues from experimental GVHD. Understanding the complex relationships between gut microbiota-metabolites-host tisses axis provides crucial insight into the pathogenesis of GVHD and advances the development of new therapeutic approaches.